MicroRNAs dysregulated in multiple sclerosis affect the differentiation of CG-4 cells, an oligodendrocyte progenitor cell line - Perdaens, Océane; Bottemanne, Pauline; van Pesch, Vincent (Frontiers in Cellular Neuroscience, 2024)
Demyelination is one of the hallmarks of multiple sclerosis (MS). While remyelination occurs during the course of the disease, it is incomplete from the start and strongly decreases with its progression, mainly due to the harm on oligodendrocyte progenitor cells (OPCs), causing irreversible neurological deficits and contributing to neurodegeneration. Therapeutic strategies promoting remyelination are still very preliminary and lack within the current treatment panel of MS. In a previous study we identified 21 microRNAs dysregulated mostly in the CSF of relapsing and/or remitting MS patients. Here, we observed that among these, the majority of 13 transfected microRNA mimics decreased the differentiation of an OPC cell line called CG-4. We further demonstrate, by RNA sequencing and independent RT-qPCR analyses, that miR-33-3p, miR-34c-5p, and miR-124-5p, arrest OPC differentiation at a late progenitor stage and miR-145-5p at a premyelinating stage as evidenced by the downregulation of premyelinating oligodendrocyte (OL) (Tcf7l2, Cnp [except for miR-145-5p]) and mature OL (Plp1, Mbp, Mobp) markers, whereas only miR-214-3p promotes OPC differentiation. We further propose a comprehensive exploration of their change in cell fate through Gene Ontology enrichment analysis. We finally confirm by RT-qPCR analyses the downregulation of several predicted mRNA targets for each microRNA that possibly support their effect on OPC differentiation by very distinctive mechanisms, of which some are still unexplored in OPC/OL physiology. We hereby open new perspectives in the research on OPC differentiation and on the pathophysiology of demyelination/remyelination, and possibly even in the search for new remyelinating therapeutic strategies in the scope of MS.